Liquid Crystals - Kumar Choudhury, Pankaj; Ibrahim, Abdel-Baset M.A (IntechOpen, 2022)
The exotic electromagnetic properties of liquid crystals can be harnessed for many technological applications in general, and in the photonics industries in particular. In addition, the varying molecular structures of crystals make them prudent for chemical industries as well. Liquid Crystals presents the basics of liquid crystals as well as discusses their applications in optics and field sensing. The book also discusses the interfacing of liquid crystal displays and the programming required for these displays.